ANALISIS TINGKAT PENGETAHUAN DAN SIKAP POSTUR KERJA PT KOMATSU REMANUFACTURING ASIA - Ramdan, Muhamad; Yuliana, Lina; Farhandi, Faisal (IDENTIFIKASI, 2022)
ABSTRACT This study aims to determine whether there is a relationship between the level of knowledge and work posture attitudes of employees at PT Komatsu Remanufacturing Asia. The benefits of this research can be used as information for companies about work attitudes that are at risk of injury to the musculoskeletal area. Then it can be taken into consideration by the company to make repairs so as to protect workers from musculoskeletal injuries and Occupational Diseases (PAK) caused by musculoskeletal injuries. This research method uses a quantitative approach with collection techniques and uses questionnaires and observations. The results of the REBA (Rapid Entire Body Assessment) questionnaire and observation checklist were converted into numbers so that statistical techniques could be used to analyze the results, then tested using the Bivariate Spearman test using SPSS for Windows 25. The results showed that there was an influence but had a degree of relationship. the “weak” relationship between knowledge and attitudes towards safe work postures at PT Komatsu Remanufacturing Asia.